Carbon remineralization in the Amazon-Guianas tropical mobile mudbelt: A sedimentary incinerator - Aller, R. C.; Blair, N. E. (Continental Shelf Research, 2006)
The Amazon River spawns a vast mobile mudbelt extending similar to 1600 km from the equator to the Orinoco delta. Deposits along the Amazon-Guianas coastline are characterized by some of the highest C-org remineralization rates reported for estuarine, deltaic, or shelf deposits, however, paradoxically, except where stabilized by mangroves or intertidal algal mats, they are usually suboxic and nonsulfidic. A combination of tides, wind-driven waves, and coastal currents forms massive fluid muds and mobile surface sediment layers similar to 0.5-2m, thick which are dynamically refluxed and frequently reoxidized. Overall, the seabed functions as a periodically mixed batch reactor, efficiently remineralizing organic matter in a gigantic sedimentary incinerator of global importance. Amazon River material entering the head of this dynamic dispersal system carries an initial terrestrial sedimentary Corg loading of similar to 0.7 mg Cm-2 particle surface area. Total C-org loading is lowered to similar to 0.2 mg Cm-2 in the proximal delta topset, similar to 60-70% of which remains of terrestrial origin. Loading decreases further to 0.12-0.14 mg Cm-2 (similar to 60% terrestrial) in mudbanks similar to 600 km downdrift along French Guiana, values comparable to those found in the oligotrophic deepsea. DOC/Sigma CO2 ratios in pore waters of French Guiana mudbanks indicate that > 90% of metabolized organic substrates are completely oxidized. Within the Amazon delta topset at the head of the dispersal system, both terrestrial and marine organic matter contribute substantially to early diagenetic remineralization, although reactive marine substrate dominates (similar to 60-70%). The conditional rate constant for terrestrial C-org in the delta topset is similar to 0.2 a(-1). As sedimentary C-org is depleted during transit, marine sources become virtually the exclusive substrate for remineralization except very near the mangrove shoreline. The delta C-13 and Delta C-14 values of pore water Sigma CO2 in mudbanks demonstrate that the primary source of remineralized organic matter within similar to 1 km of shore is a small quantity of bomb signature marine plankton (+ 80 parts per thousand). Thus, fresh marine organic material is constantly entrained into mobile deposits and increasingly drives early diagenetic reactions along the transit path. Relatively refractory terrestrial C-org is lost more slowly but steadily during sedimentary refluxing and suboxic diagenesis. Amazon Fan deposits formed during low sea level stand largely bypassed this suboxic sedimentary incinerator and stored material with up to similar to 3X the modern high stand inner shelf C-org load (Keil et al., 1997b. Proceedings of the Ocean Drilling Program, Scientific Results. Vol. 155. pp. 531-537). Sedimentary dynamics, including frequency and magnitude of remobilization, and the nature of dispersal systems are clearly key controls on diagenetic processes, biogeochemical cycling, and global C storage along the continental margins. (c) 2006 Elsevier Ltd. All rights reserved.
id: 979; 109UE Times Cited:28 Cited References Count:93